Doktrini kibernetskega vojskovanja Rusije in Ukrajine - Rebrica, Patrik (Teorija in praksa, 2025)
Cyber warfare has introduced a new dimension to modern conflicts whereby the risks are greater than ever before as critical infrastructure, financial systems, and personal data become targets. The boundaries between the digital and physical worlds are becoming blurred, adding to the need for effective cybersecurity. The purpose of the work is to examine the impact of cyber warfare in the Russo-Ukrainian war. Understanding doctrines and tactics helps enhance national security, protect civilians, and maintain the stability of global digital infrastructure, and permits the development of strategies to mitigate risks in future conflicts.
Keywords: cybernetics; defence; doctrine; doktrina; kibernetika; obramba; vojna; vojskovanje; war; warfare